PENERAPAN MODEL ALTMAN (Z-SCORE) UNTUK MEMPREDIKSI KEBANGKRUTAN PADA INDUSTRI TEKSTIL DAN PRODUK TEKSTIL YANG TERDAFTAR DI BEI PERIODE 2009-2011 - Aswinda Salatin (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
This study aims to determine the company's financial performance that will be used to predict the possibility of bankruptcy at a company. Research using bankruptcy prediction models Altman (Z-Score). This research is descriptive quantitative approach. Altman developed a model allowing to predict bankruptcy for up to two years before it was time. Five ratios used are working capital to total assets, retained earnings to total assets, earnings before interest and taxes to total assets, market value of equity to book value of total debts, and sales to total assets.The study population was Textiles and Textile Products industry of Indonesia Go-Public and still listing. The sample used in this study were six Textiles and Textile Products industry (TPT) are always listed on the Indonesia Stock Exchange (BEI) in the year 2009-2011. The results of a study of six textile industry listed on the Stock Exchange showed that six companies are predicted to bankruptcy.Of the five variables used to predict bankruptcy, X3 variables that most influence the bankruptcies. The management should immediately take the necessary measures to correct and prevent the condition of the company so that the company can continue its business and generating profits. Key Words: Application of Altman Model (Z-Score), Bankruptcy Prediction in TPT Industry.